Car driving, air travel or more sustainable transport? Socio-psychological factors in everyday mobility and long-distance leisure travel. (July 2022) - Dütschke, Elisabeth; Engel, Lukas; Theis, Anna; Hanss, Daniel
Highlights: Around 2000 respondents reported about transport mode use for everyday mobility and long-distance leisure travel. We identify socio-economic and socio-psychological correlates of using sustainable transport modes. Socio-economic factors are stronger predictors for everyday mobility than for long-distance leisure travel. Among the socio-psychological variables, perceived behavioural control plays a crucial role. Abstract: A decrease in unsustainable mobility is needed for everyday mobility as well as for leisure travel, here defined as overnight travel for longer distances, in order to reach decarbonisation goals. So far studies that explicitly target both are rare. The survey presented here examines socio-psychological and socio-economic variables that might influence individual use of more or less sustainable transport modes for everyday mobility and for long-distance leisure travel. It was conducted through an online questionnaire among a sample of n = 1982 residents in Germany, representative of the German population holding a drivers' license in terms of age and gender. Use of transport mode (the dependent variable) was operationalized by contrasting (a) car travel (considered the unsustainable mode) versus other transport modes for everyday mobility and (b) plane trips (the unsustainable mode) versus other transport modes for long-distance leisure travel. Respondents reported past transport mode use and intentions for future transport. Independent variables were transport habits, self-efficacy beliefs, awareness of need, awareness of consequences, perceived behavioural control, personal and social norms, non-moral aspects, emotional consequences, further negative or positive consequences (i.e., the socio-psychological variables), and socio-economic variables. Together, the socio-psychological and socio-economic variables explained significant portions of the variance in the dependent variables. Socio-economic factors were stronger predictors for everyday mobility than for long-distance leisure travel. Perceived behavioural control was an overall consistent and strong predictor, increasing the likelihood of more sustainable travel mode use. We discuss entry points for interventions based on our findings.